Nitrogen use efficiency reimagined: advancements in agronomic, ecophysiological, and molecular strategies - Reddy, Marthala Bhuvaneswar; Sravani, Pokala; Kumar, Sudhir; Rajawat, Mahendra Vikram Singh; Jaiswal, Durgesh Kumar; Dhar, Shiva; Azman, Elisa Azura; Garg, Kamal; Kumar, Sanjeev (Taylor and Francis, 2025)
Enhancing nitrogen use efficiency (NUE) in agriculture requires a holistic approach spanning agronomy, physiology, and molecular biology. Nitrogen is crucial for optimal plant growth and increased crop yield, playing a pivotal role in modern agricultural practices. While inorganic nitrogen fertilizers have boosted global food production, the disparity between nitrogen application and efficiency has led to intricate environmental issues. NUE serves as a vital gauge for evaluating fertilizer nitrogen utilization in crop cultivation, with metrics like partial factor productivity and agronomic efficiency providing valuable insights. Root morphology, transporter activity, and physiological processes regulate nitrogen uptake and utilization efficiency, constituting essential factors in NUE optimization. However, nitrogen losses within agroecosystems, such as denitrification and leaching, present significant challenges. To address this, innovative agronomic techniques like Site-Specific Nutrient Management and precision agriculture, along with genetic interventions including transgenic methods and CRISPR, offer promising solutions. By integrating agronomic practices, physiological understandings, and genetic enhancements, we can augment NUE, leading to increased crop yields, reduced nutrient losses, and minimized environmental impacts. This multidimensional strategy holds the key to a resilient and productive agricultural future.